If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2(x + -9) = 82 Reorder the terms: 8x + 2(-9 + x) = 82 8x + (-9 * 2 + x * 2) = 82 8x + (-18 + 2x) = 82 Reorder the terms: -18 + 8x + 2x = 82 Combine like terms: 8x + 2x = 10x -18 + 10x = 82 Solving -18 + 10x = 82 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 10x = 82 + 18 Combine like terms: -18 + 18 = 0 0 + 10x = 82 + 18 10x = 82 + 18 Combine like terms: 82 + 18 = 100 10x = 100 Divide each side by '10'. x = 10 Simplifying x = 10
| -7x=-4 | | 93x=27 | | 0=5.1x+0.3x | | 8x+12(x-9)=82 | | 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 | | 5/6*2/3*2/7 |